Conocemos las diversas celebraciones de la familia - Arias Farro, Gilda Rosalina (2019)
This work is focused on students recognizing, valuing and respecting the family customs that are part of their training and identity._x000D_ The session entitled We know the various celebrations of the family, which corresponds to the area of Social Staff, was developed in the Second Degree of Primary Education, taking into account the competence of Build your identity, in which the capacity that the student recognizes himself as a member of a specific cultural socio-collective and has a sense of belonging to his family,. educational institution and community._x000D_ In the preparation of the learning session, the pedagogical processes of a session and didactics of the area have been taken into account in order to promote the active and meaningful participation of students during the development of it using it as an instrument a list of checks to verify the purpose of the new learning.